2014
DOI: 10.1074/jbc.m113.526855
|View full text |Cite
|
Sign up to set email alerts
|

Human Krüppel-related 3 (HKR3) Is a Novel Transcription Activator of Alternate Reading Frame (ARF) Gene

Abstract: Background: HKR3, one of the POK family proteins, is uncharacterized in its biological function. Results: HKR3 activates transcription of ARF by interfering with FBI-1 binding on ARF promoter. Conclusion: HKR3 inhibits cell proliferation by activating transcription of ARF. Significance: HKR3 is a novel transcription activator of ARF, antagonizing proto oncogene FBI-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…However, the regulation of HKR3 expression involved more gene and protein changes in more areas compared to those for hTERT, which is involved in telomere synthesis in the nucleus. This differential expression can be explained by the fact that HKR3 is a telomeric zinc finger-associated protein that controls telomere elongation and acts as a transcription activator [19], regulating the expression of various genes. Previous studies have reported that HKR3 inhibits ARF expression and cell proliferation in the ARF region [36,37], indicating that among various tumor-suppressing functions, HKR3 also acts as a regulator of the cell cycle, which is controlled by ARF and cell proliferation [19,36,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the regulation of HKR3 expression involved more gene and protein changes in more areas compared to those for hTERT, which is involved in telomere synthesis in the nucleus. This differential expression can be explained by the fact that HKR3 is a telomeric zinc finger-associated protein that controls telomere elongation and acts as a transcription activator [19], regulating the expression of various genes. Previous studies have reported that HKR3 inhibits ARF expression and cell proliferation in the ARF region [36,37], indicating that among various tumor-suppressing functions, HKR3 also acts as a regulator of the cell cycle, which is controlled by ARF and cell proliferation [19,36,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was confirmed that steroidogenic acute regulatory protein (StAR) was the factor that increased the expression of hTERT, the negative activity of hTERT is regulated by HKR3 (ZBTB48), but it is not clear [17]. HKR3 is a relatively uncharacterized POK family protein with a POZ-domain and 11 zinc finger domains [18,19]. HKR3 is ubiquitously expressed in human tissues [20].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were fixed with formaldehyde (final 1%) to cross-link proteins to DNA promoters. ChIP and ChIP-reChIP procedures were then performed as reported elsewhere ( 20 ). For detection of transcription factor binding, chromatin was immunoprecipitated with antibodies against p53, FLAG-tag, His-tag and Myc-tag.…”
Section: Methodsmentioning
confidence: 99%
“…MIZ-1, a potent transcriptional activator of CDKN1A ( 11 ), interacts with various oncoproteins, such as c-MYC, BCL6, ZBTB4 and GFI-1, to repress transcription of genes involved in cellular differentiation and metabolism ( 6 , 11 13 ). Recently, some novel POK family proteins have been characterized as transcriptional regulators of genes that control cell proliferation ( 14 20 ). Although POK family proteins appear to play key roles in the various cell regulatory programs described above, the functions of many of the above-mentioned POK family proteins remain largely unknown ( 3 ).…”
Section: Introductionmentioning
confidence: 99%